Organizational Justice And Organizational Citizenship Behavior Among Librarians - Ismail, Fadillah; Wei, Chan Shiau; Mohamad Azmi, Nur Azia Hazida (Gae, 2025)
Organizational justice plays an essential role in affecting extra role behavior which is above and beyond formal role requirements. It is believe that there is a relationship between organizational justice and organizational citizenship behavior. Therefore, this study was aimed to identify the level of organizational justice and the level of organizational citizenship as well as to investigate the relationship between organizational justice and organizational citizenship behavior among librarian at Public Library in the State of Selangor. This study is a cross-sectional study whereby data is collected from a total of 105 respondents. The data were analyzed using Statistical Package for Social Science version 22. Descriptive and inferential statistics were used for data analysis. Findings showed that there was a moderate level of organizational justice and a high level of organizational citizenship behavior among the public librarian. Result also reveals that there is a significant strong positive relationship between all dimension of organizational justice and organizational citizenship behavior among the public librarian with interactional justice was found to have the strongest relationship with organizational citizenship behavior followed by distributive and procedural justice. Therefore, it is necessary to enhance justice in organization by looking into the organizational policy and holding training programs for employees to foster them the tendency to display voluntary behaviors.